PENGUKURAN KUALITAS LAYANAN JARINGAN KABEL SERAT OPTIK LINK BENCULUK-JIMBARAN - Ratih Devyanti, Putu; Sukadarmika, Gede; Oka Saputra, Komang (Jurnal SPEKTRUM, 2021)
Optical fiber is a telecommunication transmission medium that has a high bandwidth and bit rate so that it can meet the needs of today's information services with high reliability and efficiency. Optical fiber applications are increasingly widespread for underwater networks, terrestrial networks, metropolitan and regional network coverage, also small-scale networks included. Optical fiber communication system has internal and external factors that affect the quality of network performance. Those factors possibly able to reduce the performance of the optical fiber networks. Then, can cause attenuation and other transmission losses. In an effort to prevent sudden and significant deterioration in the quality of a network, it is necessary to carry out periodic maintenance activities such as measuring the quality of scheduled fiber optic cable network services. These maintenance activities can help determine the decision to increase network capacity at a later date. The service quality parameters that often measured are the attenuation of the transmission and the received signal power (power receive). This study examines the measurement of attenuation of the Benculuk-Jimbaran fiber optic cable using OTDR EXFO FTB-150. The measurement results of 8 idle cores were analyzed using Optisystem 7.0 and the calculation of total attenuation and receive sensitivity. The measurement results of core 1 to core 12 have total attenuation ranging from 29, 942 dB - 30.654 dB at a distance of 169, 646 km - 170, 323 km. The value of power received on cores 1 to 12 has a value ranging from -17,339 dBm - 18,204 dBm, where all idle cores fulfill the receive sensitivity requirements set by ITU-T, which is greater than -28 dBm. Based on the performance                                                                                                                 analysis according to total attenuation and power receive parameters, the Benculuk-Jimbaran fiber optic link network has good performance quality.